Using Dictyostelium to Develop Therapeutics for Acute Respiratory Distress Syndrome - Kirolos, Sara A.; Rijal, Ramesh; Consalvo, Kristen M.; Gomer, Richard H. (Frontiers in Cell and Developmental Biology, 2021)
Acute respiratory distress syndrome (ARDS) involves damage to lungs causing an influx of neutrophils from the blood into the lung airspaces, and the neutrophils causing further damage, which attracts more neutrophils in a vicious cycle. There are ~190,000 cases of ARDS per year in the US, and because of the lack of therapeutics, the mortality rate is ~40%. Repelling neutrophils out of the lung airspaces, or simply preventing neutrophil entry, is a potential therapeutic. In this minireview, we discuss how our lab noticed that a protein called AprA secreted by growing Dictyostelium cells functions as a repellent for Dictyostelium cells, causing cells to move away from a source of AprA. We then found that AprA has structural similarity to a human secreted protein called dipeptidyl peptidase IV (DPPIV), and that DPPIV is a repellent for human neutrophils. In animal models of ARDS, inhalation of DPPIV or DPPIV mimetics blocks neutrophil influx into the lungs. To move DPPIV or DPPIV mimetics into the clinic, we need to know how this repulsion works to understand possible drug interactions and side effects. Combining biochemistry and genetics in Dictyostelium to elucidate the AprA signal transduction pathway, followed by drug studies in human neutrophils to determine similarities and differences between neutrophil and Dictyostelium chemorepulsion, will hopefully lead to the safe use of DPPIV or DPPIV mimetics in the clinic.